Reform of Civil Procedural Legislation of Ukraine and Problems of its Implementation - Shtefan, Olena (Teisė, 2022)
New rules for transferring the case from one court to another are being investigated, the conclusion on expanding the competence of the court on this issue is substantiated. The most problematic requirements for the content of the claim, which are not provided with legal and organizational mechanisms, are considered. Particular attention was paid to the problem of implementing “cassation filters”, which have undergone additional changes since the main reform strengthens them. It is proved that this problem is closely related to another one – the problem of defining a certain legal concepts, substantiates a significant expansion of the scope of judicial discretion in determining the grounds for cassation appeal in a particular case. The article considers the possibility of referring to the decisions of the European Court of Human Rights as the sources of civil procedural law of Ukraine. The problem of administering justice under martial law received separate consideration. It is concluded that the evaluation of the effectiveness of judicial reform involves its critical consideration by both science and practice, generalization and analysis of law enforcement practice will provide grounds for a final assessment of the quality of reform.